The growth of seaweed (Eucheuma cottoni) at different fertilizing doses in the waters of the village of Ghonebalano, Duruka District, Muna Regency, Indonesia - Fendi Fendi; La Lili; Abdul Rakhfid; Rochmady Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2019)
The study was conducted aiming to test different fertilizer doses on the optimal growth rate of Eucheuma cottonii seaweed. The study was conducted from July to August 2016 in the waters of Ghonebalano Village, Duruka District, Muna Regency, Southeast Sulawesi. The study used NPK fertilizer with the composition of the element nitrogen (N) 15%, phosphate (P2O5) 15%, and potassium (K2O) 15%. The study used a Randomized Block Design (RBD) with 3 (three) levels of fertilizer doses and 3 (three) groups so that the number of experimental units was 9 (nine) units. While the treatments tested in the study were treatment A (without fertilizer/control), treatment B (fertilizer dose 1 g/L), and treatment C (fertilizer dose 2 g/L). The results showed that the difference in fertilizer dose significantly affected the growth rate of Eucheuma cottonii seaweed. A dosage of 2 g/L of fertilizer gives the best rate of growth of Eucheuma cottonii seaweed while the water quality at the study site shows that it is still in the optimal range for the growth of Eucheuma cottonii seaweed.